2016
DOI: 10.15420/aer.2016.18.2
|View full text |Cite
|
Sign up to set email alerts
|

Classification, Electrophysiological Features and Therapy of Atrioventricular Nodal Reentrant Tachycardia

Abstract: Atrioventricular nodal reentrant tachycardia (AVNRT) denotes re-entry in the area of the AV node, and represents the most common regular arrhythmia in the human.1 Although several models have been proposed to explain the mechanism of the arrhythmia in the context of the complex anatomy and the anisotropic properties of the atrioventricular (AV) node and its atrial extensions (see Figure 1), 2 the actual circuit of AVNRT still remains elusive. Recent studies suggest a three-dimensional AV node with greater vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 67 publications
0
26
0
3
Order By: Relevance
“…AV nodal reentrant tachycardia (AVNRT) with variable antegrade AV or retrograde ventriculoatrial (VA) relationships are infrequently observed and might be misdiagnosed as atrial tachycardia (AT) . Dual or multiple AV nodal slow pathways or common pathways, could provide an electrophysiological basis for the development of irregular arrhythmia in the presence of AVNRT. Therefore, the main differential diagnosis of an irregular arrhythmia is between the AVNRT and perinodal ATs .…”
Section: Discussionmentioning
confidence: 99%
“…AV nodal reentrant tachycardia (AVNRT) with variable antegrade AV or retrograde ventriculoatrial (VA) relationships are infrequently observed and might be misdiagnosed as atrial tachycardia (AT) . Dual or multiple AV nodal slow pathways or common pathways, could provide an electrophysiological basis for the development of irregular arrhythmia in the presence of AVNRT. Therefore, the main differential diagnosis of an irregular arrhythmia is between the AVNRT and perinodal ATs .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐eight patients who underwent radiofrequency catheter ablation of the antegrade slow pathway between January 2013 and September 2016 in our institute were enrolled in this study. The type of AVNRT was classified into a slow‐fast AVNRT, which was defined as having an A‐H interval/His‐atrial (H‐A) interval ratio (A‐H/H‐A) of >1 and H‐A interval <70 ms along with a tachycardia induction mode with an antegrade jump‐up phenomenon based on the previous reports . Patients with uncommon AVNRT, including fast‐slow AVNRT and slow‐slow AVNRT, were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…val <70 ms along with a tachycardia induction mode with an antegrade jump-up phenomenon based on the previous reports. 6 Patients with uncommon AVNRT, including fast-slow AVNRT and slow-slow AVNRT, were excluded. The patients with nonsustained AVNRT, which could not be evaluated by an electrophysiological study (EPS) during the tachycardia, were excluded.…”
Section: Interval/his-atrial (H-a) Interval Ratio (A-h/h-a) Of >1 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…
Although the exact circuit of atrioventricular nodal re-entrant tachycardia (AVNRT) still eludes us, AVNRT is the most common regular arrhythmia in humans, and therefore the most commonly encountered during ablation attempts for regular tachycardias. [1][2][3][4] Catheter ablation for AVNRT is the current treatment of choice in symptomatic patients. It reduces arrhythmia-related hospitalisations and costs, and substantially improves quality of life.
…”
mentioning
confidence: 99%